FRI0499 A multinational qualitative study in giant cell arteritis: patient perceptions of diagnosis, treatment, impact on health-related quality of life and contextual factors. (12th June 2018) - Robson, J.C.; Almeida, C.; Dawson, J.; Bromhead, A.; Mackie, S.L.; Hill, C.; Hoon, E.; Davis, C.; Greenwood, R.; Luqmani, R.; Dasgupta, B.; Guly, C.; et al.
Abstract : Background: Giant cell arteritis (GCA) is the commonest form of systemic vasculitis caused by inflammation of the blood vessels around the head and neck, with the highest incidence in women aged 70–79 years (7.4 per 10 000 person-years). Patients present with headache, jaw claudication and polymyalgia rheumatica with visual loss in 20%. Treatment is with high dose glucocorticoids. Objectives: Identify and define the range of patient experiences in relation to GCA, and effects on health related quality of life in patients from the United Kingdom and Australia. Methods: Semi-structured qualitative interviews with patients from the UK and Australia explored health-related quality of life and patient perspectives on the experience of GCA. Interviews were recorded, transcribed and analysed. Patients were purposively sampled to include both genders, a range of disease durations and organ involvement (visual loss and large vessel involvement). Data were analysed with inductive thematic analysis and managed using NVivo 10. The sample size was determined by the point at which no new substantive themes emerged. Results: Thirty-one interviews were conducted. Demographics and disease features shown in table 1. Individual sub-codes were identified then grouped into overarching themes: "Anxieties around getting a diagnosis of GCA", "Description of symptoms related to GCA and its treatment", "Lack of bodily strength, stability and stamina; difficulties with completing daily tasks", "Difficulties with participating in social activities, work and caring roles", "Not feeling normal and impact on general perception of health", "Anxiety and fear of the future". Contextual factors impacted on how patients experienced GCA including "Response to treatment and adverse effects", "Receiving support from family, friends and health care workers", "Adopting successful self-management techniques, e.g. keeping fit and active" and "Presence of pre-existing co-morbidities and development of secondary conditions e.g. cardiovascular disease, osteoporosis or diabetes". Conclusions: Patients with GCA have described a range of themes of interest in relation to their disease. These data could be used as the basis of developing a patient reported measure of outcome in GCA. Disclosure of Interest: None declared